The Effectiveness of Interactive Augmented Reality for Preschool Science Education - Noraniza, Samat; Rahmah, Mokhtar; Muhammad Iman, Mohd Salleh; Ngahzaifa, Ab. Ghani; Bayuaji, Luhur; Siti Normaziah, Ihsan (2015)
The use of multimedia technology in education has inspired the new invention for teaching and learning purposes. This paper presents the research of Augmented Reality (AR) which is a part of multimedia technology, specifically focused on preschool kids. The objectives of this research are to design and develop an educational augmented reality application for preschool kids; design and produce physical book that supports AP application; and study the effectiveness of AR technology in kids’ learning. In the process of completing this research, ADDIE methodology has been applied. The courseware namely AR Science for Kids (ARkids) is developed based on the science syllabus for preschool set up by Tabika Perpaduan, Department of National Unity and Integration Department, Prime Minister Department. ARkids has been tested to 20 preschool kids and the output indicates that 86.6% of the respondents show very good acceptance of the AR application. This shows that AR is one of the best technologies that can be put to good use in aiding preschool subjects, especially science. The interaction with 3D objects can attract the users’ attention improve their learning experience. It is hoped that ARkids can help improving the preschool education in Malaysia, and inspire many more inventions that make good use of technologies.